2013
DOI: 10.1177/0960327113506237
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of l-carnitine on tamoxifen toxicity and oncolytic activity

Abstract: The aim of this study was to investigate the protective effect of l-carnitine (l-CAR) in tamoxifen (TAM)-induced toxicity and antitumor activity. Adult female rats were randomly divided into four groups. Group I was served as control, groups II and III were treated with TAM (10 mg/kg, periorally) and l-CAR (300 mg/kg, intraperitoneally), respectively, while group IV was treated with both compounds. The treatment continued daily for 28 days. Administration of TAM resulted in significant increase in ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Because a greater increase in ALT than in AST is an indicator of hepatocellular damage, the seen TAM‐induced changes seem not to be related with possible liver damage, as was seen by other authors, using intraperitoneal injection of TAM with a dose of 1 mg/kg for 5 consecutive days to mouse models of steatosis, but with difference in body weight and fat composition and/or with the antiestrogenic action of TAM. It was previously reported that the administration of TAM (10 mg/kg/d) for 28 days induced an increase of triglycerides, cholesterol, AST, and ALT levels …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Because a greater increase in ALT than in AST is an indicator of hepatocellular damage, the seen TAM‐induced changes seem not to be related with possible liver damage, as was seen by other authors, using intraperitoneal injection of TAM with a dose of 1 mg/kg for 5 consecutive days to mouse models of steatosis, but with difference in body weight and fat composition and/or with the antiestrogenic action of TAM. It was previously reported that the administration of TAM (10 mg/kg/d) for 28 days induced an increase of triglycerides, cholesterol, AST, and ALT levels …”
Section: Discussionmentioning
confidence: 94%
“…Several investigations have addressed the effects of TAM on liver toxicity and on metabolic homeostasis, but its action remains a challenge in cancer therapy outcomes. Indeed, despite its recognizable activity in reducing breast cancer risk, TAM actions can represent a continuous encumbrance to hepatic functions throughout the long‐term treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, administration of LC in diabetic rats decreases oxidative stress as evident from the GSH and SOD levels. Ibrahim et al reported that LC increases GSH levels and the activity of antioxidant enzymes such as SOD, too (59). Furthermore, reduction in the level of antioxidation compounds in the diabetic group and elevation in the treated diabetic group with LC show scavenging effects of LC against ROS production during oxidative stress (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The mice were randomly allocated into five groups (six rats each): (i) normal control group; (ii) SEC control vehicle: 0.2 mL (5 × 10 6 /mL) of live EAC cells were injected subcutaneously into the thigh of the lower limb of each mouse and distilled water and ethanol were administered; (iii) SEC+TAM: mice were injected with tamoxifen (10 mg/kg bd. wt., IP) dissolved in distilled water once daily for 14 days [74]; (iv) SEC+ORL: mice were injected with ORL (240 mg/kg bd. wt., IP) dissolved in 10% ethanol once daily for 14 days (Saleh et al, 2019); (v) SEC+ORL-NC: SEC mice were injected with ORL-NC (240 mg/kg bd.…”
Section: Experimental Designmentioning
confidence: 99%